Theoretical and Experimental Insights into CdO-ZnO Nanocomposites for Gas Sensing (International Journal of Scientific Research in Science and Technology, 2025)
Metal oxide nanocomposites have emerged as promising materials for gas sensing applications due to their enhanced surface area, electronic properties, and catalytic activity. This study investigates the ethanol gas sensing characteristics of CdO-ZnO nanocomposites synthesized using the sol-gel method. Structural, morphological, and compositional analyses through XRD, FESEM, EDS, and FTIR confirmed the successful formation of well-integrated CdO-ZnO nanocomposites. The gas sensing response was evaluated for CdO-ZnO nanocomposites out of which CdO-ZnO (70:30) ratio demonstrating the highest gas response (67.23) towards ethanol (50 ppm) at room temperature, optimal response-recovery characteristics, and long-term stability at room temperature. The adsorption mechanism of ethanol gas was analyzed using the Langmuir adsorption model, which showed a strong correlation with experimental data, validating a monolayer adsorption process. The gas response exhibited a sharp increase at lower ethanol concentrations, reaching saturation beyond 50 ppm, confirming the presence of finite active adsorption sites. The smallest particle size (~28 nm) observed for the CdO-ZnO (70:30) composition enhanced the surface-to-volume ratio, leading to improved gas adsorption and electron transfer. Gas sensing study CdO-ZnO (70:30) contribute to the development of high-performance ethanol gas sensors with superior selectivity, high gas response, and long-term operational stability.
Keywords: CdO-ZnO nanocomposite; Ethanol gas sensing; Langmuir adsorption model; Metal oxide sensor; Sol-gel synthesis; Gas response saturation